Digital Guru Embodiment, Technology, and the Transmission of Traditional Knowledge in Kerala - Finnian M. M. Gerety (Asian Ethnology, 2018)
The Nambudiri Brahmins of the South Indian state of Kerala transmit what may be the oldest surviving musical culture in South Asia, a fixed oral tradition of sacred songs used in ritual (Sāmaveda). Without recourse to written notation, Nambudiri practitioners teach songs face-to-face, using their voices and a distinctive system of hand gestures to convey melodies to their students. This embodied transmission of knowledge is further shaped by hereditary and social requirements that dictate who may teach, who may learn, and in what circumstances. As a result of such strict norms for teaching, and under the pressure of broader social changes, Nambudiri Sāmaveda in the late twentieth and early twenty-first centuries has declined to the point where only a single active line of normative transmission exists. This article presents a case study of the close bond and evolving pedagogical relationship between the aging guru (teacher) and student involved in this unique transmission, highlighting the integration of digital technology into their lessons, and examining the impact of this innovation on textual, pedagogical, and ritual authority. The “digital guru”—in the form of an archive of audio- and video-recordings— aids recall and restores a sense of authority to the transmission of Sāmaveda, and yet the living guru is ultimately a presence that cannot be replaced.